Operationalisation of the European Union security policy - Orlić Dejan (Međunarodni Problemi, 2006)
The author explores the operational capability of the European defense policy in the last 3 years. From the creation and adoption of the European Security Strategy, the European Union has made several specific steps in the development of the European Security and Defense Policy. Despite the disagreements with the United States about Iraq and the internal divisions in the "New and Old Europe" EU has shown the ability to set new military and civilian goals, make a small, but effective battle group concept for crisis management and conflict prevention as well as the European Defense Agency. The author also describes the main operations and missions of EU in the world, ranging from the Balkans and Africa to the Middle East and Eastern Asia. Finally, the paper analyses the Constitution for Europe and the articles concerning ESDP.